Investigation of the emission characteristics of iso-butanol additives on methanol-gasoline blends using spark ignition engine - Hazim, Sharudin; Nik Rosli, Abdullah; M. N. A. M., Yusof; H. H., Masjuki; Ali, Obed Majeed (UiTM Press, 2017)
Lower emissions of spark ignition engine can be achieved by using alcohol fuels such as methanol as it is more environmental advantage over fossil fuel. The methanol fuels can be further improved by added with iso-butanol as it have higher energy content and able to displace more gasoline fuel. Nevertheless, the research on the addition of lower ratio iso-butanol in methanol-gasoline blends specifically on exhaust emission is still not investigated thoroughly. Therefore, this study will focus on investigating the effect of iso-butanol additive on methanol-gasoline blends on the emission characteristics of spark ignition engine. The lower percentage (5%) of methanol-gasoline fuels was added with lower ratio of iso-butanol (5-15%) with 5% of volume increment. The experimental test were carried out on a 1.6-litre four-cylinder spark ignition engine at a fixed speed of 4000 rpm with increasing engine load form 10 Nm until 100 Nm. The results showed that the iso-butanol additive in methanol-gasoline blends was efficient to reduce the carbon monoxide (CO) and unburned hydrocarbon (HC) formation compared to base fuel. Among all tested fuels, M5B15 (Iso-butanol 15% + Methanol 5% + Gasoline 80%) blend gave lower CO and HC emissions by 12.45% and 16.18% at 100 Nm. Meanwhile, oxides of nitrogen (NOx) and carbon dioxide (CO2) emissions were higher for all methanol-gasoline blends with iso-butanol additives compared with that base gasoline. M5B15 blends gives higher emissions of NOx and CO2 by 11.45% and 11.74% at 100 Nm. This study summarized that iso-butanol additives can be applied in low percentage methanol-gasoline blends without any modification on the current existing engine, therefore reducing any serious environment impact.